ЗОНА ХІМІЧНИХ РЕАКЦІЙ ПРИ ДЕТОНАЦІЙНОМУ СИНТЕЗІ НАНОАЛМАЗІВ НА ФАЗОВІЙ ДІАГРАМІ ВУГЛЕЦЮ - Долматов, Валерий; Дорохов, Александр; Муллюмаки, Веса; Веханен, Аско; Марчуков, Валерий (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2019)
The purpose of this work is to determine the optimal temperature and pressure behind the detonation wave front to obtain nanodiamonds with more than 6% wt. yield. The charge was obtained mainly by pressing, the explosion was carried out in a conservation chamber with a capacity of 2.14 m3. The temperature and pressure in the Chapman-Jouguet plane, oxygen balance and charge density were analyzed. The optimal zone for the production of detonation nanodiamonds (DNDs) in the carbon phase diagram (P, T-conditions) has been refined. The required explosion temperature is 3800-4300 K, the pressure in the zone of chemical reactions is 24-30 GPa, the optimum oxygen balance is from -42 to -53%, the charge density is ≥1.6 g / cm3. The research results should be used in assessing the possibility of obtaining DNDs from explosives at known pressures and temperatures of the explosion, the calculated oxygen balance and the recommended charge density. The value of this work lies in the extreme simplicity of the calculations of the required parameters.